2008
DOI: 10.1037/0893-164x.22.1.47
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity of substance dependence and depression: Role of life stress and self-efficacy in sustaining abstinence.

Abstract: The authors examined life stress and self-efficacy as predictors of time to relapse for 113 adults with comorbid major depressive disorder and alcohol and/or substance dependence in a randomized clinical trial comparing 2 psychotherapy interventions (integrated cognitive- behavioral therapy and 12-step facilitation therapy). Life stress, self-efficacy, and substance use were assessed at treatment entry, 12 weeks (mid-treatment), and 24 weeks (end of treatment). Time to relapse was defined as the number of days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
74
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(80 citation statements)
references
References 77 publications
(95 reference statements)
3
74
1
2
Order By: Relevance
“…According to Bandura, drug abuse behavior, on the one hand, is learned by imitation and reinforcement in the area of interpersonal relationships, and on the other hand, is influenced by individual factors such as self-efficacy and individual beliefs (Bandura, 1993). Research findings also suggest that there is a significant relationship between self-efficacy and drug abuse in the adolescents, the more is the self-efficacy, the less is the tendency toward drug abuse (Dolan, Rosemarie, Martin, & Rohsenow, 2008;Tate et al, 2008;McKellar, Ilgen, Moos, & Moos, 2008;Ibrahim et al, 2011).…”
mentioning
confidence: 57%
“…According to Bandura, drug abuse behavior, on the one hand, is learned by imitation and reinforcement in the area of interpersonal relationships, and on the other hand, is influenced by individual factors such as self-efficacy and individual beliefs (Bandura, 1993). Research findings also suggest that there is a significant relationship between self-efficacy and drug abuse in the adolescents, the more is the self-efficacy, the less is the tendency toward drug abuse (Dolan, Rosemarie, Martin, & Rohsenow, 2008;Tate et al, 2008;McKellar, Ilgen, Moos, & Moos, 2008;Ibrahim et al, 2011).…”
mentioning
confidence: 57%
“…La relación entre autoeficacia y resultados en el tratamiento de dependientes a cocaína ha sido examinada en varios estudios (Dolan, Martin y Rohsenow, 2008;Hser et al, 2006;Tate et al, 2008;Wong, Anthony, Mongeon, Badger, y Higgins, 2004). En dichos trabajos se concluye que aquellos pacientes que presentan niveles altos de autoeficacia parecen mostrar una mayor protección frente a la recaída.…”
Section: Autoeficaciaunclassified
“…A measure of craving, the 'Obsessive Compulsive Drinking Scale' (Anton, Moak, & Latham, 1996) has been found to predict relapse in those with depression or bipolar disorder and alcohol problems (Farren & McElroy, 2010), thus this could be used to identify high risk clients. Stresses such as relationship and housing problems predict relapse in those with depression and substance misuse (Tate et al, 2008), thus coping skills to deal with these are important. Finally, the majority of relapses occur within two months after treatment (Tate, et al, 2008), so close monitoring after discharge and booster sessions are indicated.…”
Section: Predictors Of Outcomementioning
confidence: 99%
“…Stresses such as relationship and housing problems predict relapse in those with depression and substance misuse (Tate et al, 2008), thus coping skills to deal with these are important. Finally, the majority of relapses occur within two months after treatment (Tate, et al, 2008), so close monitoring after discharge and booster sessions are indicated. A number of gender differences are present in those with dual diagnosis.…”
Section: Predictors Of Outcomementioning
confidence: 99%